On the concept of an agricultural holding in European Union law - Germanò, Alberto (Przegląd Prawa Rolnego, 2024)
The author analyses the question that has been referred to the Court of Justice on whether a winemakers’ organisation which cultivates vineyards leased from other parties and uses the work of other persons under its control and responsibility can be defined as a “holding.” Proper interpretation of this is required in order to lawfully apply the specific terms set out in Annex VI of Delegated Regulation 2019/33 in accordance with Article 54(1)(2) of that Regulation.